History of American Economy, 13th Edition - Gary M. Walton; Hugh Rockoff (Cengage Learning, 2017)
Ever wonder how the American economy became the most powerful one in the world? Tying America's past to the economic policies of today and beyond, the popular HISTORY OF THE AMERICAN ECONOMY, 13E answers this critical question and more, presenting events chronologically for easy understanding. This prestigious book has been used by more learners than any other of its kind in the U.S. Market-leading HISTORY OF THE AMERICAN ECONOMY has helped generations of learners understand how the American economy evolved. Completely updated with recent research by economic historians, this trusted book ties this country's past to the policies and debates of today and beyond. Visual aids, tables and graphs reinforce learning and encourage interest in the study of economic history.